(untitled) (The Review of Diabetic Studies, 2025)
Nursing practice in emergency and high-risk environments is critical to ensuring timely, safe, and effective patient care under conditions of uncertainty, high acuity, and resource constraints. Nurses in these settings play a central role in rapid assessment, triage, continuous monitoring, emergency interventions, and coordination of care, while simultaneously facing significant occupational and psychological risks. This review aims to synthesize current evidence on the clinical effectiveness of nursing practice in emergency and high-risk environments and to examine the key workforce challenges that influence care quality and safety. A comprehensive review of recent literature was conducted across major healthcare databases, focusing on studies published in the last decade that evaluated nursing-led practices, patient outcomes, and workforce-related factors. The findings indicate that effective nursing practices are strongly associated with improved patient safety, reduced adverse events, and enhanced operational efficiency. However, persistent workforce challenges—including burnout, workplace violence, staffing shortages, and fatigue—negatively impact performance, retention, and care outcomes. Addressing these challenges through organizational support, training, and policy-level interventions is essential to sustaining high-quality emergency nursing care. The review highlights the need for integrated strategies that align clinical excellence with workforce wellbeing.